Evaluation of the Technical Efficiency of Taiwan’s Milkfish Polyculture in Consideration of Differences in Culturing Models and Environments - Yung-Hsiang Lu; Yi-Wei Huang; Jia-Jan Lee; Sheng-Ju Huang (Fishes, 2022)
Taiwan has cultured milkfish for longer than hundreds of years. Given its long and narrow terrain surrounded by sea and location in a subtropical monsoon area, it has developed a unique culture bounded by the Erren River in the south. The Yunjianan area in the north is cold in winter and thus follows the “current year harvest” culturing model. In contrast, the Gaoping area in the south is warmer in winter and follows the “overwinter harvest” culturing model. This paper evaluated the production efficiency by using the stochastic metafrontier production model and the multi-input-multi-output distance function using input from in-person interviews with 100 current year harvest farmers and 70 overwinter harvest farmers from 2017 to 2019. In the first stage, the environmental variables of various regions were internalized into the model to obtain the group technical efficiency (GTE) of different farming models. In the second stage, the common environmental variables were re-internalized to evaluate the metafrontier technical efficiency (MTE) of both culturing modes. In this way, the technical efficiency and production technology of the two different culturing model are reasonably evaluated by taking into account not only the difference between their input and output, but also their environmental difference during their farming periods. The results show that in spite of the environmental difference between th two culturing models, shallower pond, smaller size of fish fry and lower shrimp density should make culturing more technically efficient. When cultured in a common environment, the lower the temperature, the worse the culture efficiency is. It indicated that milkfish are highly sensitive to low temperature. Therefore, the MTE and technical gap rate (TGR) of current year harvest farming are significantly higher than those of overwinter harvest farming. Finally, the regression analysis showed that the younger the farmers were, the lower the average pond age was, the larger the freshwater culture area was, and the greater the experience in fish farming was. Thus, the relatively better the MTE is; the younger the farmers, the higher the education level is and the more years of experience in fish farming they have, thus the relatively better the production technology level is.